A-kinase interacting protein 1 is sufficiently expressed and positively associates with WHO grade, meanwhile predicts unfavorable overall survival independently in glioma patients. Issue 4 (29th January 2021) - Shen, Songbo; Yao, Yiqun
Abstract : Abstract: The present study aimed to investigate the association of A-kinase interacting protein 1 (AKIP1) with clinical characteristics, and further explore the prognostic value of AKIP1 in glioma patients. Totally 168 glioma patients who underwent tumor resection were analyzed, and their tumor tissue specimens were acquired for the detection of AKIP1 expression by immunohistochemistry (IHC), which was scored by a semi-quantitative method considering staining intensity and staining density. According to AKIP1 expression in tumor tissues of glioma patients, there were 65 (38.7%) patients with AKIP1 low expression (IHC score 0–3), 48 (28.6%) patients with AKIP1 high + expression (IHC score 4–6), 42 (25.0%) patients with AKIP1 high++ expression (IHC score 7–9) and 13 (7.7%) patients with AKIP1 high+++ expression (IHC score 10–12), respectively. AKIP1 expression was positively associated with World Health Organization grade. Overall survival (OS) was the lowest in the patients with AKIP1 high+++ expression, followed by those with AKIP1 high++ expression and those with AKIP1 high+ expression, and highest in those with AKIP1 low expression. Further subgroup analysis exhibited that AKIP1 expression was negatively associated with OS especially in high-grade glioma patients. In addition, AKIP1 expression was negatively associated with OS in all subgroups of patients with/without adjuvant radiotherapy, with/without adjuvant chemotherapy. Further multivariate Cox's regression exhibited that AKIP1 high expression was an independent predictive factor for worse OS. AKIP1 presents with the potential to be a novel biomarker for tumor management and prognosis surveillance in glioma patients.